2018
DOI: 10.3168/jds.2017-12936
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an enzymatic route using a food-grade recombinant Bacillus subtilis for the production and purification of epilactose from lactose

Abstract: Lactose is a main by-product in the cheese industry. Many attempts have been made to convert the lactose to high value-added products, including epilactose. Epilactose is a valuable prebiotic and can be epimerized from lactose with cellobiose 2-epimerase (CEase). The objective of the present work was to construct a food-grade recombinant Bacillus subtilis that produces CEase from Thermoanaerobacterium saccharolyticum. The CEase was expressed in B. subtilis without antibiotic resistance genes. After fermentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
(47 reference statements)
2
12
0
Order By: Relevance
“…The yeast cell treated epilactose/glucose/galactose mixed syrup showed nearly 100% elimination on glucose and galactose while epilactose was not metabolized. This was in accordance with the conclusion that epilactose was a non‐digestible food ingredient 40 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The yeast cell treated epilactose/glucose/galactose mixed syrup showed nearly 100% elimination on glucose and galactose while epilactose was not metabolized. This was in accordance with the conclusion that epilactose was a non‐digestible food ingredient 40 …”
Section: Discussionsupporting
confidence: 92%
“…As a comparison, Chen et al . obtained 88.5 g L −1 epilactose from 300 g L −1 lactose, which was catalyzed by ethanol permeabilized Bacillus subtilis 1A751 whole cells 40 . Saburi et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Krewinkel et al [53] reported that cellobiose 2-epimerase from the mesophiles Flavobacterium johnsoniae and Pedobacter heparinus are able to catalyze the synthesis of epilactose with a reaction yield around 33%, without formation of side product. More recently, Chen et al [54] produced epilactose from cheese whey (300 g/L) using the cellobiose 2-epimerase from Thermoanaerobacterium saccharolyticum expressed in Bacillus subtilis. Then, they hydrolyzed the remaining lactose with the β-galactosidase form Bifidobacterium bifidum and removed the monosaccharides using selective fermentation with Saccharomyces cerevisiae.…”
Section: Other Lactose-derived Health Promoting Bioactive Compoundsmentioning
confidence: 99%